La sostenibilidad ambiental bajo el modelo neoliberal en el sector minero en Colombia (INGE@UAN - TENDENCIAS EN LA INGENIERÍA, 2012)
The present document makes reference to the implementation of the neoliberal model in our country and the impact that it has had in the Colombian economy. Also, one is like unsustainability example the mining practices in our country if we followed with our present norms.
Keywords: Sustainable development; economic development; models of development; strategies of development; neoliberal model